2017
DOI: 10.1007/s12035-017-0631-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Glia Interplay and Increased miRNA-155 as Promising Markers to Track ALS at an Early Stage

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease of unknown cause. Absence of specific targets and biomarkers compromise the development of new therapeutic strategies and of innovative tools to stratify patients and assess their responses to treatment. Here, we investigate changes in neuroprotective-neuroinflammatory actions in the spinal cord of SOD1 mice, at presymptomatic and symptomatic stages to identify stage-specific biomarkers and potential targets. Results showed that in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 74 publications
12
105
1
Order By: Relevance
“…Among other miRNAs suspected to contribute to ALS pathology is the altered expression of miR-146a and miR-21in the SC and brainstem of ALS transgenic mice [81]. Similarly to these authors we also found reduced miR-146a levels in the cortical homogenates, a feature not observed in the SC from the same mSOD1 mice model, in either stage 1 or stage 2 [19]. Again, our results contrast with other studies showing an elevated miR-146a expression in patient SC samples [82], suggesting the existence of phenotypic changes in ALS patients and rodent models, while supporting the new label of precision medicine.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Among other miRNAs suspected to contribute to ALS pathology is the altered expression of miR-146a and miR-21in the SC and brainstem of ALS transgenic mice [81]. Similarly to these authors we also found reduced miR-146a levels in the cortical homogenates, a feature not observed in the SC from the same mSOD1 mice model, in either stage 1 or stage 2 [19]. Again, our results contrast with other studies showing an elevated miR-146a expression in patient SC samples [82], suggesting the existence of phenotypic changes in ALS patients and rodent models, while supporting the new label of precision medicine.…”
Section: Discussionsupporting
confidence: 88%
“…1b). WT mice only exhibited one band corresponding to the native mouse SOD1, as previously described [19]. Now considering the phosphorylated eIF2α and the transcription factor ATF4, we observed that both were reduced, but only in mSOD1 mice at stage 2 (p < 0.01, Fig.…”
Section: Cortical Accumulation Of Sod1 Protein Precedes Downregulatiosupporting
confidence: 83%
See 3 more Smart Citations